Replication concerns in sports and exercise science: a narrative review of selected methodological issues in the field. Issue 12 (14th December 2022) - Mesquida, Cristian; Murphy, Jennifer; Lakens, Daniël; Warne, Joe
Abstract : Known methodological issues such as publication bias, questionable research practices and studies with underpowered designs are known to decrease the replicability of study findings. The presence of such issues has been widely established across different research fields, especially in psychology. Their presence raised the first concerns that the replicability of study findings could be low and led researchers to conduct large replication projects. These replication projects revealed that a significant portion of original study findings could not be replicated, giving rise to the conceptualization of the replication crisis. Although previous research in the field of sports and exercise science has identified the first warning signs, such as an overwhelming proportion of significant findings, small sample sizes and lack of data availability, their possible consequences for the replicability of our field have been overlooked. We discuss the consequences of the above issues on the replicability of our field and offer potential solutions to improve replicability.